The experiences and support needs of people with intellectual disabilities who identify as LGBT: A review of the literature - MC CANN, EDWARD (My University, 2016)
Background: People who identify as lesbian, gay, bisexual and transgender (LGBT) can face many challenges in society including accessing education, care and support appropriate to individual needs. However, there is a growing and evolving evidence base about the specific needs of people with intellectual disabilities (ID) in this regard. Aims: The aim of this review was to explore the experiences of people with ID who identified as LGBT through an examination of studies that addressed their views and highlighted specific issues, concerns and service responses. Methods and procedures: A comprehensive search of relevant databases from February 1995 to February 2015 was conducted. Studies were identified that met specific criteria that included: empirical peer reviewed studies, the use of recognised research methods and focused on people with ID whom identified as LGBT. The search yielded 161 papers in total. The search was narrowed and 37 papers were screened using rigorous inclusion and exclusion criteria. Finally, 14 papers were considered suitable for the review. Outcomes and results: The data were analysed and key themes identified that included accessing health services, gender and sexual identity, attitudes of people with ID regarding their LGBT status, and education, supports and therapeutic interventions. Conclusions and implications: There is a need for service providers and carers to be more responsive to the concerns of people with ID who identify as LGBT to improve their health and well-being by reducing stigma and discrimination and by increasing awareness of their care and support needs. The implications are discussed in terms of policy, education, research and practice developments.
PUBLISHED
Keywords: Lesbian, gay, bisexual, transgender, intellectual disability; GLBT; intellectual disability; developmental disability; Identities in Transformation; Inclusive Society